Diurnal cycles of solar radiation and forests evergreenness in Central Africa - (:unkn) unknown (My University, 2018)
The sunlight conditions prevailing in Central Africa, and their potential impact on forests traits and functioning, have never been fully explored. Using satellite estimates documenting mostly the period 2005-2013, and accounting for scale interactions between the diurnal and annual cycles, we demonstrate that the seasonality of sunlight levels strongly vary across Central Africa forests. Gabon stands out with a main dry season strongly light-deficient, cool and moist. An original map of terra firme forest types developed by CIRAD shows that most of the evergreen forests of Central Africa develop in Gabon. We postulate that despite a mean annual precipitation amount below 2000 mm/yr, the Gabonese climate can harbor most of the evergreen forests of Central Africa because of a heavy cloudiness which reduces the water demand and decreases the direct to diffuse light ratio.These findings and the methodology developed pave the way for further analyses of the past and future changes in the light-deficient climates of Western Central Africa and the vulnerability of the evergreen forests to these changes.
Keywords: African Research